Microbial carbon recycling: an underestimated process controlling soil carbon dynamics - Part 2: A C3-C4 vegetation change field labelling experiment - Basler, A; Dippold, M; Helfrich, M; Dyckmans, J (Biogeosciences, 2015)
The mean residence times (MRT) of different compound classes of soil organic matter (SOM) do not match their inherent recalcitrance to decomposition. One reason for this is the stabilization within the soil matrix, but recycling, i.e. the reuse of "old" organic material to form new biomass may also play a role as it uncouples the residence times of organic matter from the lifetime of discrete molecules in soil. We analysed soil sugar dynamics in a natural 30-year old labelling experiment after a wheat-maize vegetation change to determine the extent of recycling and stabilization by assessing differences in turnover dynamics between plant and microbial-derived sugars: while plant-derived sugars are only affected by stabilization processes, microbial sugars may be subject to both, stabilization and recycling. To disentangle the dynamics of soil sugars, we separated different density fractions (free particulate organic matter (fPOM), light occluded particulate organic matter (≤ 1.6 g cm-3; oPOM1.6), dense occluded particulate organic matter (≤ 2 g cm-3; oPOM2) and mineral-associated organic matter (> 2 g cm-3; mineral)) of a silty loam under long-term wheat and maize cultivation. The isotopic signature of neutral sugars was measured by high pressure liquid chromatography coupled to isotope ratio mass spectrometry (HPLC/IRMS), after hydrolysis with 4 M Trifluoroacetic acid. While apparent MRT of sugars were comparable to total organic carbon in the bulk soil and mineral fraction, the apparent MRT of sugar carbon in the oPOM fractions were considerably lower than those of the total carbon of these fractions. This indicates that oPOM formation was fuelled by microbial activity feeding on new plant input. In the bulk soil, MRT of the mainly plant-derived xylose were significantly lower than those of mainly microbial-derived sugars like galactose, rhamnose, fucose, indicating that recycling of organic matter is an important factor regulating organic matter dynamics in soil.